Phased Impacts of China’s Dual-Credit Policy on R&D - Li, Xu; Xiong, Qing Y. (Frontiers in Energy Research, 2021)
As a sustainability policy in emerging markets, the dual-credit policy was implemented in China to promote automakers expanding investment in research and development, and ultimately achieve the energy-saving and emission-reduction goals of the auto industry. We regard the dual-credit policy as a quasi-natural experiment, use the difference-in-difference model to divide Chinese automakers into an experimental group (the passenger vehicle group) and a control group (the commercial vehicle group), and analyze the impacts of the dual-credit policy in the brewing period (2014–2016) and the implementation period on the scale, intensity, and structure of research and development investment. We found that the dual-credit policy has significantly promoted the research and development investment of automakers, and the heterogeneity of automakers has a moderating effect on the policy effects. In addition, we also found that there are certain differences in the significance and stability of the effects of the dual-credit policy during the brewing period and the implementation period. Finally, we presented some management insights into the response to the dual-credit policy.